2020
DOI: 10.1177/1753944720931637
|View full text |Cite
|
Sign up to set email alerts
|

Current status of white coat hypertension: where are we?

Abstract: White coat hypertension (WCH) is characterised by an elevated clinic blood pressure (BP) with normal ambulatory or home BP. It is well recognised in clinical practice and occurs in approximately one-third of untreated patients with elevated clinic BP. Current evidence suggests that WCH is associated with cardiovascular risk factors, including the development of sustained hypertension and the presence of target organ damage. However, its effects on cardiovascular outcomes remain a matter of debate. There is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 55 publications
0
25
0
3
Order By: Relevance
“…Изолированная гипертония «белого халата» (изолированная офисная/клиническая АГ) -это состояние, при котором при повторных посещениях лечебного учреждения АД оказывается повышенным, а вне его, при суточном мониторировании АД или ДМАД, -нормальным [10][11][12]. Данное состояние выявляется примерно у 13% людей с АГ [16]. Правильно выбрали определение понятия 63,6% респондентов (СПО от 57,8 до 81% в разных центрах, p=0,176, V Крамера 0,131; В.…”
Section: Conclusion the Results Of The Study Indicate An Insufficient...unclassified
“…Изолированная гипертония «белого халата» (изолированная офисная/клиническая АГ) -это состояние, при котором при повторных посещениях лечебного учреждения АД оказывается повышенным, а вне его, при суточном мониторировании АД или ДМАД, -нормальным [10][11][12]. Данное состояние выявляется примерно у 13% людей с АГ [16]. Правильно выбрали определение понятия 63,6% респондентов (СПО от 57,8 до 81% в разных центрах, p=0,176, V Крамера 0,131; В.…”
Section: Conclusion the Results Of The Study Indicate An Insufficient...unclassified
“…As a consequence, the detection of this phenotype would avoid unnecessary treatment intensification, with may have related side effects and lead to an increase in costs. Some particular characteristics have been described in subjects with white coat hypertension and/or WUCH [19][20][21], especially when ABPM is used as the out-ofoffice BP measurement method. For instance, in the Spanish ABPM registry, Banegas et al found that, in treated hypertensives, age ≥ 60 years, female sex, non-smokers, the absence of diabetes and having a lesser target-organ damage were independent predictors of WUCH [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying the WCE are still poorly understood, hypotheses point towards psychological and emotional factors such as stress and anxiety ( Cobos et al, 2015 ; Nuredini et al, 2020 ). According to Grassi et al ( 1999 ), this is an alert reaction similar to the defence reactions observed in animals when faced with emotional stressors.…”
Section: Effects Of the White Coat On The Patient (“White Coat Effect”)mentioning
confidence: 99%